1989
DOI: 10.1021/bi00437a041
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman investigations of site-directed mutants of myoglobin: effects of distal histidine replacement

Abstract: The resonance Raman spectra of met-, deoxy-, and (carbonmonoxy)myoglobin (MbCO) are studied as a function of amino acid replacement at the distal histidine-E7 position. The synthetic wild type is found to be spectroscopically identical with the native material. The methionine and glycine replacements do not affect the met or deoxy spectra but do lead to distinct changes in the nu Fe-CO region of the MbCO spectrum. The native MbCO displays a pH-dependent population redistribution of the nu Fe-CO modes, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
221
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(251 citation statements)
references
References 33 publications
28
221
1
1
Order By: Relevance
“…There are two CO absorption bands at 1,932 cm Ϫ1 and 1,968 cm Ϫ1 . These bands have been called the N 3 (lower frequency) and N 0 (higher frequency) conformers, respectively, in analogy to the A 3 and A 0 bands of Mb (27,29). The significant width of the CO stretching bands of Ngb and their Gaussian shapes imply structural heterogeneity associated with each protein substate that is sensed by the CO bound to the active site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two CO absorption bands at 1,932 cm Ϫ1 and 1,968 cm Ϫ1 . These bands have been called the N 3 (lower frequency) and N 0 (higher frequency) conformers, respectively, in analogy to the A 3 and A 0 bands of Mb (27,29). The significant width of the CO stretching bands of Ngb and their Gaussian shapes imply structural heterogeneity associated with each protein substate that is sensed by the CO bound to the active site.…”
Section: Resultsmentioning
confidence: 99%
“…1). Experiments, theory, and molecular dynamics simulations have shown that both the local and global coupling between protein structure and the CO vibrational transition frequency is mainly through the electric field along the CO bond (19,20,24,29,30,(35)(36)(37). The protein residues range from charged, to polar, to nonpolar.…”
Section: Resultsmentioning
confidence: 99%
“…In the spectrum of wt-Ngb (solid curve), there are two CO bands at 1,932 cm Ϫ1 and 1,968 cm Ϫ1 . These have been called the N 3 (lower frequency) and N 0 (higher frequency) conformers, respectively, in analogy to the A 3 and A 0 bands of Mb (26)(27)(28). The significant width of the CO-stretching bands of Ngb and their Gaussian shapes implies that there is structural heterogeneity associated with each protein substate.…”
Section: Resultsmentioning
confidence: 99%
“…Carbonmonoxy-myoglobin (MbCO) has been extensively studied both experimentally [47][48][49][50][51][52][53][54][55][56] and computationally. [57][58][59][60] Myoglobin (Mb) is a small globular heme protein weighing approximately 17 kDa that is found in mammalian muscle tissue.…”
Section: D Vibrational Echo Experiments a Illustration Of The mentioning
confidence: 99%